Pengaruh Perhatian Orang Tua dan Motivasi Belajar terhadap Kedisiplinan Siswa Sekolah Menengah Atas - Didit Darmawan; Ahmad Syauqi Albaar; Adinda Oktavia (Universitas Palangka Raya, 2026)
Low student discipline, such as frequenttardiness, non-compliance with rules, and negligence in completing assignments,is an important topic that needs to be studied. This study aims to analyze the influence of parental attention and learning motivation onthe discipline of high school students. The research method usedis a Systematic Literature Review (SLR) with a descriptive qualitative approach. Data were obtained from various articles, journals, and previous studiesrelevant to the topic in the range of 2012–2025. The results of the studyshow that parental attention as an external factor, throughsupervision, guidance, and emotional support, has a positive andsignificant effect on the formation of student discipline. On the other hand, learning motivationas an internal factor, both intrinsic in the form of motivation to achieve andperseverance, as well as extrinsic in the form of rewards and environmental support,has been proven to encourage students to be orderly, consistent, and responsible intheir studies. These findings confirm that the synergy between parental attention andlearning motivation contributes greatly to shaping student discipline, whichultimately has a positive impact on improving academic achievement andcreating an orderly and conducive school climate.